Healing the Curse of the grosero Husband: Women's Health Seeking and Pentecostal Conversion in Oaxaca, Mexico - Everett, Margaret Carter (Journal of contemporary religion, 2015)
Drawing on anthropological research in Oaxaca, Mexico, this article describes the role of health seeking in women's experiences with Pentecostal conversion. The present study confirms that Pentecostalism's promise of reforming problematic male behavior is a significant draw for women. Women's stories of conversion are strikingly consistent in their accounts of male drinking, womanizing, and domestic violence. However, the findings also demonstrate that when efforts to domesticate men failand they often dowomen still find significant ways in which Pentecostalism addresses suffering. The study provides a unique contribution to the literature by exploring that paradox in detail.